Mary’s role in the repudiation of their beliefs of Pagans, Jews and Moors - Snow, Joseph T. (2020)
The Cantigas de Santa Maria of Alfonso X, king of Castile and León (1252-1284) contains 420 miracles and praise songs for the Virgin Mary. We have identified 41 with Jewish protagonists, 51 with Moors and 5 with pagans. Ten of these − three with Jews, 6 with Moors and one with a pagan − have been selected for treatment as they involve conversions to Christianity. Side by side, the actions of these miracle narrations are supported by what Alfonso declared to be their treatment in his law code, the Siete Partidas. There, laws regarding how non-Christians are to be treated along with specific laws about their conversion to the Christian law of the land are taken into account. Members of their religions may not impede conversions under penalty of death by fire. Both the Cantigas and the Siete Partidas reflect one another faithfully.   Bibliography: Studies ALFONSO X – Cantigas de Santa Maria. Ed. Walter Mettmann, Clásicos Castalia 134, 172, 178. Madrid: Castalia, 1986-1989. ALFONSO X – Las Siete Partidas. Vol. 5. Underworlds: the Dead, the Criminal and the Marginalized. Trans. Samuel Parsons Scott and edited by Robert I. Burns; S. J. Philadelphia: University of Pe nnsylvania Press, 2001. BURNS, Robert I.; S. J. – Alfonso the Learned, Emperor of Culture (1284-1984). A special number of Thought 60 (1985). BURNS, Robert I.; S. J. – Emperor of Culture: Alfonso the Learned and his Thirteenth Century Renaissance. Philadelphia: University of Pennsylvania Press, 1990. CARPENTER, Dwayne E. – Alfonso X and the Jews; An Edition of and Commentary on Siete Partidas 7:24 “de los judíos”. Berkeley & Los Angeles: Univ. of California Press, 1986. KULP-HILL, Kathleen (trans.) – Songs of Holy Mary of Alfonso X. A Translation of the Cantigas de Santa Maria. Tempe, Arizona: Arizona Center for Medieval and Renaissance Studies, 2000. MARTÍNEZ, H. Salvador – La convivencia en España del siglo XIII. Perspectivas alfonsíes. Madrid: Polifemo, 2006. SCOTT, Samuel Parsons – See Alfonso X, The Siete Partidas (above).